Production of bioethanol from tapioca starch using saccharomyces serevisiae : effect of inoculum concentration and temperature - Muhd Bashori, Abu Bakar (2008)
The inoculum concentration of Saccharomyces cerevisiae yeast and the temperature on ethanol production were studied. The optimum conditions of starch hydrolysis such as substrate and enzymes concentration, pH and the time required for the enzymatic action were fixed during the entire process study. The two-step enzymatic hydrolysis of tapioca by commercially available α-amylase and glucoamylase were employed. The fermentation process was run in 250 mL shake flasks. Based on the results, the highest yield of ethanol was 20.7 wt% which was produced at 36°C for the effect of temperature study. However, for inoculum concentration study, at 20% (v/v), the yield of ethanol was 21 wt% which was the highest.